Mejoramiento de procesos de manufactura utilizando Kanban (2015)
This paper presents the application of the Kanban methodology and analysis of the effect that this can generate in a manufacturing of distribution transformers. By applying the proposed methodology can be improved production scheduling, with the aim of reducing the amount of product in process is not used, so that inventory is reduced. To analyze the effect of applying the Kanban methodology in the company, the simulation technique was used, for which the current process and proposed to the rules of the Kanban methodology is modeled. From these results that yield modeling, it shows that there is an improvement in production lines where kanban methodology is used.